Heat rate deviation analysis of a Coal-Fired Power Plant (CFPP) with the influence of Applicable Coal Prices (ACP) - Jasbeer Singh, Manmit Singh; Abdul Jalil, Nawal Aswan; Abdul Rahim, Sharafiz; Zulkefli, Zamir Aimaduddin; Hasini, Hasril (Universiti Putra Malaysia Press, 2023)
The assessment of a Coal-Fired Power Plant (CFPP) performance is an intricate process that involves the determination of Heat Rate (HR) deviations of current operational parameters from baseline or target values. This study focuses on HR deviations of a CFPP based on the Applicable Coal Price (ACP), and the influence of the ACP price on daily losses or gains are thoroughly analyzed for key performance parameters for three fixed ACP of RM12, 18, and 24 per GJ. This paper mainly investigates key parameters and related equipment that significantly affect the HR of the CFPP and ranks the parameters affecting HR from most significant to least significant. The baseline or target values are obtained from the plant commissioning manuals and the Performance Guarantee Test (PGT). Actual real-life operational data from a 700MWn CFPP is utilized to improve the accuracy and confidence levels of the results obtained. It was found that at the nominal operating baseload, the most significant negative HR deviation is for the Rotary Air Heater (RAH) gas exit temperature with a negative HR deviation of -137.9 kJ/kWh leading to an annual loss of RM17.6 million at ACP of RM24/GJ while the superheater and reheater spray flows are contributing least to the HR deviation. This analysis highlighting the impact of key parameters affecting the performance enables plant operations and maintenance teams to focus on such parameters to mitigate losses.